Basal haemoglobin levels as prognostic factor for early death in elderly patients with a hip fracture – A twenty year observation study. Issue 6 (June 2015) - Kovar, Florian M.; Endler, Georg; Wagner, Oswald F.; Jaindl, Manuela
Abstract Introduction Hip fractures are a significant cause of mortality and morbidity in the elderly. This study investigated the relationship between initial haemoglobin (Hb) levels and a prognostic parameter for outcome in those patients. Patients and methods A total of 3595 consecutive patients with diagnosed hip fractures were included in our study (72.2% females). Anaemia was defined according to WHO criteria, with according subgroups mild, moderate and severe anaemia. Data collection was performed prospectively and statistical evaluation was performed retrospectively. Results Mean follow up in our study group was 11.2 ± 0.3 months. The mean age of our study group was 78.5 years (SEM ± 0.2 years). To facilitate analysis, patients were divided in two groups: ≤84 years (60.1%) and ≥85 years (39.9%). Mortality <12 months was 12.2% (n = 439). In our study population lower Hb levels ad admission were associated with a markedly elevated short-term mortality. In a multivariate logistic regression model adjusted for age and sex, mild anaemia at admission caused a 1.5 (CI: 1.1–1.9), moderate anaemia a 2.6 (95 CI: 2.0–3.4), and severe anaemia a 3.6 (CI: 1.8–6.9) fold increase in three months mortality compared to patients without anaemia. Total lymphocyte count (1.2 ± 0) did not show any differences between the subgroups. Conclusion Those findings in our study population with 3595 patients over a period of twenty years have proven that initial Hb levels are a useful and cost effective parameter to predict mortality in elderly patients with a hip fracture. This prognostic factor may help to increase the outcome of elderly patients with a hip fracture.